Dynamic Characteristics of Air Cycle Machine Rotor System - Dongjiang Han; Long Hao; Jinfu Yang (Shock and Vibration)
Parameters optimization in the critical speed region has the important influence on operational stability of an air cycle machine. Effects of bearing stiffness and unbalanced exciting force on critical speed and response characteristics are investigated by the modal method and harmonic response analysis. Resonance separation phenomenon in the critical speed region is analyzed in detail. When difference exists in the phase of unbalanced exciting force, resonance separation appears in the conical whirling speed region. The characteristics after resonance separation are closely related to the phase difference value and amplitude of unbalanced exciting force. The paper provides theoretical and experimental foundations for resonance separation analysis and also provides data support for dynamic balance and dynamic design of the rotor system.